No evidence for additional systemic eosinophil mobilization during exacerbations in patients with COPD and chronic bronchitis but no allergy - Andersson, Anders; Andelid, Kristina; Brundin, Bettina; Ekberg-Jansson, Ann; Lindén, Anders (Frontiers in Medicine, 2025)
BackgroundThere is published evidence that a modest increase in blood eosinophils during stable COPD indicates future risk for exacerbations and a potential utility of inhaled corticosteroids. This has been perceived as an argument for targeting systemic eosinophil mobilization to prevent exacerbations in COPD, but there are no published data on systemic eosinophil mobilization during exacerbations in patients without allergy.MethodsWe investigated long-term tobacco smokers (LTS: ≥10 pack-years) with COPD and chronic bronchitis (COPD-CB; GOLD stage 1–4; n = 47) but no allergy; LTS without COPD and CB (LTS; n = 10), and healthy never-smokers (HNS; n = 10) during stable disease for cross-sectional comparisons. For longitudinal comparisons, we followed the COPD-CB group for 15 months during stable disease and exacerbations, excluding samples affected by systemic corticosteroids. We quantified blood concentrations of eosinophils, the activity marker eosinophilic cationic protein (ECP) and the chemokine interleukin (IL)-4.ResultsDuring stable disease, the concentrations of eosinophils were similar for the COPD-CB and the LTS group, although higher than in the HNS group. The concentrations of ECP and IL-4 were not markedly different in the COPD-CB and LTS groups either. During exacerbations, the concentrations of eosinophils, ECP and IL-4 were not further increased, and there was even a mathematical trend towards a decrease for these concentrations.ConclusionThe clinical evidence presented here suggests that, by average, there is no additional mobilization of eosinophils during exacerbations in patients with COPD and chronic bronchitis but no allergy. Thus, in this common phenotype, the immunological rationale for targeting systemic eosinophils during exacerbations remains unaccounted for, which motivates verification studies in large cohorts stratified for allergy and chronic bronchitis.